Early reduction of BCR-ABL mRNA transcript levels predicts cytogenetic response in chronic phase CML patients treated with imatinib after failure of interferon α - Merx, Kirsten; Müller, Martin Christian; Kreil, Sebastian; Lahaye, T.; Paschka, Peter; Schoch, C.; Weißer, Andreas; Kuhn, C.; Berger, Ute; Gschaidmeier, Harald; Hehlmann, Rüdiger; Hochhaus, Andreas (Leukemia, 2002)
The degree of tumor load reduction as measured by cytogenetic response is an important prognostic factor for chronic myelogenous leukemia (CML) patients on therapy. We sought to determine whether BCR-ABL transcript levels can predict chromosomal response. Residual disease was evaluated in 120 CML patients in chronic phase (CP) treated with the selective tyrosine kinase inhibitor imatinib after resistance or intolerance to interferon α (IFN). Median time of therapy was 401 days (range 111-704). BCR-ABL and total ABL transcripts were measured in 486 peripheral blood (PB) specimens with a real time RT-PCR approach using fluorescent-labeled hybridization probes (LightCycler technology) and results were expressed as the ratio BCR-ABL/ABL. Cytogenetic response was determined in 3-monthly intervals: From 101 evaluable patients, 42 achieved a complete (CR, 0% Philadelphia chromosome (Ph)- positive metaphases), 18 a partial (PR, 1-34% Ph+), 13 a minor (MR, 35-94% Ph+), and 26 no response (NR, >94% Ph+). All PB samples were RT-PCR positive. The proportion of Ph+ metaphases and simultaneous BCR-ABL/ABL ratios correlated with r = 0.74, P < 0.0001. In order to investigate whether early molecular analysis may predict cytogenetic response, quantitative RT-PCR data obtained after 1 and 2 months of therapy were compared with cytogenetic response at 6 months. BCR-ABL/ABL ratios after 1 month were not predictive, but results after 2 months correlated with the consecutive cytogenetic response (P = 0.0008). The probability for a major cytogenetic response was significantly higher in patients with a BCR-ABL/ABL ratio <20% after 2 months of imatinib therapy. We conclude that: (1) quantitative determination of residual disease with real time RT-PCR is a reliable and sensitive method to monitor CML patients on imatinib therapy; (2) BCR-ABL/ABL ratios correlate well with cytogenetic response; (3) in IFN-pretreated patients all complete responders to imatinib have evidence of residual disease with the limited follow-up available; and (4) cytogenetic response at 6 months of therapy in CP patients is predictable with real time RT-PCR at 2 months.
Gesehen am 16.05.2022